Plurality of Truth in the Study of Hushuli Science (Study of Islamic Scientific Epistemology) - Supandi, Didi; Abdillah, Abdillah; Naan, Naan; Hakim, Maman Lukmanul (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
Plurality has become an endless debate by Islamic scholars in finding truth in knowledge. The study aims to analyze the plurality of truth from the perspective of hushuli science (knowledge by correspondence) and its application. The approach that researchers use is qualitative with the content analysis method, which is an analytical study of ideas or products of plurality thinking that begins with describing the primary ideas that are the object of research. Ideas are obtained from primary and secondary texts. The results concluded that there is a plurality of truth knowledge in the perspective of hushuli science. The diversity of truth is a necessity and must be accepted. This plurality of truth can be a foothold in developing tolerance among religious people. The truth of knowledge is not homogeneous but heterogeneous. This fact must be a foothold in teaching about the multiculturalism that exists in life. The results of this study are expected to be able to make a positive contribution to the life of a plural society in order to realize that plurality should not be opposed to each other but to coexist in the frame of togetherness.